Ethnomedicinal plants uses for the treatment of gastrointestinal disorders in Tribal District North Waziristan, Khyber Pakhtunkhawa, Pakistan - Rehman, Sabith; Iqbal , Zafar; Qureshi , Rahmatullah (Ethnobotany Research and Applications, 2023)
Background: The local communities of Tribal District North Waziristan rely on therapeutic plant species for their primary health care needs. The present study aimed to record the indigenous knowledge and use of therapeutic plant species to treat different gastrointestinal disorders by the local inhabitants. Methods: Ethnomedicinal data was collected through semi-structured interviews on the use of therapeutic plant species. A total of 130 informants (106 men and 24 women) were randomly selected. The data was quantitatively analyzed using Relataive Frequency of Citiation (RFC), Use Reports (UR), Fidelity Level (FL), Use Value (UV), and Family Importance Value (FIV). Results: A total of 69 medicinal plant species belonging to 36 families were recorded. Among them, Lamiaceae was the most prevalent (10 species), followed by Asteraceae (5 species), and Amaranthaceae, and Apiaceae (4 species each). The dominant growth form was the herb (62.32%), followed by tree (20.29%) and shrub (13.04%). The most common plant parts used in herbal remedies preparations were the leaves (31.51 %) and fruits (26.03 %). The leading mode of herbal recipe preparation was decoction; and the herbal medicines were administered orally. The therapeutic plant species with maximum UV values were Mentha arvensis L., Morus alba L., and Cydonia oblonga Mill. (0.83 each), followed by Withania coagulans (Stocks) Dunal in DC. (0.82). The highest RFC value was reported for Cydonia oblonga Mill. (0.37), followed by Trachyspermum ammi L. and Mentha arvensis L. (0.36) each. The species with 100% FL values were Carum carvi L., Trachyspermum ammi L., Morus alba L., and Cyndonia oblonga Mill. Conclusion: The study showed that indigenous communities still prefer therapeutic plants over allopathic drug for curing different gastrointestinal disorders. However, this invaluable traditional knowledge is presently limited to older people in the study area. There is the need to encourage younger people to engage into this knowledge and participate in its transmission to help conserve the use of medicinal plants for curing ailments in the study area. Keywords: Medicinal plants, Fidelity level, Indigenous knowledge, Gastrointestinal disorders, North Waziristan, Pakistan.